Letramento Digital: um estudo de caso em uma escola municipal de João Pessoa. - Araújo, Peterson Martins Alves (2006)
This study has as main subject Digital Literacy, which is seen as a state or condition of those who appropriate the new technologies and its hipertextual reading and writing practices through the screen. The object of analysis inside this type of literacy will be the observation on how it has been constructed among primary teachers of the Municipal Durmeval Trigueiro Mendes School in João Pessoa city. In order to achieve this objective it was made a case of study of the primary teachers (1st to 4th grade), whose descriptive and exploratory work investigates and perceives the possible problems related to the program of educative computer science adopted by the referred city. For this, the work carries through a historical passage of Educative Computer science searching its origins since a macrostructure understanding, where it is analyzed models adopted in some countries (U.S.A, France and Brazil) until reaching in the microstructural reality of João Pessoa. Then, there is a critical reflection on the changes in the pedagogical models that imply in alterations in the teachers and students role within the informational context. After that, the work goes through diverse concepts (hypertext, digital genres, alphabetization, etc) directly or indirectly related to Digital Literacy. Finally, it carries through an analysis of the data collected through interviews, observations and the context of the analyzed school, from there to generate hypotheses, critical reflections and positioning when considering the informatization program in Joao Pessoa schools.